AN ANALYSIS OF CONTENT VALIDITY IN ENGLISH MID-TERM EXAMINATION TEST ITEMS AT SIXTH GRADE AT SD IT FATMA KENANGA KOTA BENGKULU - Tania Syafutri; Elsa Viona (Corolla International Conference, 2022)
This study aims to analyze content validity in English Mid-Term examination test items at sixth grade at SD IT Fatma Kenanga Kota Bengkulu. The researcher is interested to analyze test items, especially in content validity because it is the determinant of the good or not of the test items' quality. The objectives of this research are (1) to know the English mid-term examination items at sixth grade in SD IT Fatma Kenanga Kota Bengkulu is suitable or not with the indicators of the syllabus, (2) to know the quality of validity of English mid-term examination questions that made by the English teacher in sixth grade at SD IT Fatma Kenanga Kota Bengkulu. In this research, the researcher has used Arikunto’s theory (2011) to know about the content validity level in test items. This research was used a qualitative method, especially descriptive qualitative. The facial content validity of the test items is described using descriptive qualitative analysis. As a result, (1) the conformity between exam items and the English syllabus is 50 %, (2) the content validity of the mid-term examination test items based on the result of conformity percentage is in the “satisfaction or valid enough” level is based on Arikunto (2011).